Influence of judoka height when using the seoi nage technique - Sebastião Iberes Lopes Melo; Saray Giovana dos Santos; Tatiane Piucco; Jairo Santarém Teixeira (Universidade Federal de Santa Catarina, 2013)
Judo techniques use the assumption of maximum efficiency with minimum energy expenditure, which means to try to use the strength of the opponent against himself, causing an imbalance that, associated with a technique, helps execute a throw. This study is aimed to evaluate the mechanical efficiency of the seoi nage technique applied to judokas (uke) of different heights in relation to the thrower (tori). The knee and trunk angular variation of tori was compared with the total throw time, the time to perform each phase of the technique, and the behavior and vertical variation of the trajectory of tori's center of mass (ΔCM). Ten throws using the seoi nage technique on three uke of shorter, equivalent, and taller statures compared to tori were cinematically analyzed. Theimages were recorded at 180 Hz using the Peak Motus System. The data was analyzed by descriptive statistics, ANOVA, and Tukey's post-hoc (p < 0.05). The tori's mechanical efficiency was greater when throwing a uke of a stature taller or of his same height, while the total throw time was shorter for a taller uke. The ΔCM of the tori was greater to throw a uke of a shorter stature. The conclusion is that the seoi nage technique is most effective when applied against opponents of heights equal to or taller than the tori.